The diagnostic value of the 10- and 30-second Wingate test for competitive athletes - Zajac, A.; Jarzabek, R.; Waskiewicz, Z. (The Journal of Strength and Conditioning Research, 1999)
Competitive, high-class track athletes of the strength-speed events were submitted to the 10- and 30-second versions of the Wingate test to compare the values of basic variables such as maximal power, total external work, fatigue index, and chosen physiological responses. The 24 male and female athletes performed the 2 tests with a 3-day rest period between them. The results indicate that even highly trained athletes of both sexes reach higher values of maximal power in the 10-second test. Also, peak power is reached more quickly and sustained for a shorter period of time. Power decrement in the first 10 seconds is smaller in the longer version, and total external work is less. All this indicates that the rate of energy expenditure and total energy expenditure is higher for the shorter test, which suggests the need for pacing in the longer version. High postexercise heart rate and high lactic acid concentration ollowing the 30-second Wingate test indicate a predominance of glycolytic metabolism, thus indicating that the longer version is more valuable in the evaluation of anaerobic capacity.